(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The prevalence of eating behavior disorders among adolescents in Ukraine and worldwide prompts research into identifying its psychological factors. Developing strategies for healthy eating behavior and studying the impact of family relationships and individual characteristics of adolescents on its formation are actively discussed in international research and remain a relevant topic for psychologists in Ukraine. Objective. The study aims to explore the relationship between eating behavior strategies in adolescence and early youth and coping behavior within the family interaction system. Methods. Surveying, which included collecting data on participants’ socio-demographic characteristics, the Dutch Eating Behavior Questionnaire (DEBQ), the Family Adaptability and Cohesion Scale (FACES-3), the Children’s and Adolescents’ Coping Strategies Questionnaire, and the Parent-Child Relationship Inventory. Results. The study describes the manifestation of eating behavior strategies in adolescents and identifies significant differences in the expression of emotional and restrictive eating behavior between boys and girls. Characteristics of family system functioning, such as cohesion and adaptability, were not associated with eating behavior strategies. Significant predictors of adolescents’ eating behavior strategies included parameters of their interaction with parents combined with coping strategies, particularly the avoidant strategy of fantasy thinking.Conclusions. Fantasy thinking as an avoidant coping strategy contributes to the formation of various types of eating behavior. The level of emotional eating behavior is determined by the combined influence of this coping strategy and poorly organized interaction with the father. The restrictive strategy is influenced by fantasy thinking and a low degree of seeking support for one’s actions, with gender as a moderating factor. The obtained results can be taken into account when planning individual consultations and group sessions with adolescents and young adults, specifically in the use of techniques aimed at developing awareness of their experiences in stressful life situations and the ability to endure them. Such skills will help prevent the use of the unproductive strategy of fantasy thinking.